The poetics of сolor and light in the works of the modern Tatar poet Renat Kharis - Galimullina Альфия (Turkic Studies Journal, 2022)
The work of the outstanding modern Tatar poet Renat Kharis (Renat Magsumovich Kharisov, born in 1941) - a People’s Poet of the Republic of Tatarstan, an author of more than 50 books in the Tatar, Russian, English, French, Polish, Belarusian, Bashkir, Chuvash languages is distinguished by a wide range of creative interests: his works are devoted to understanding the moral, philosophical, socio-political themes of the past and present of the Tatar people, Russia and the world community. The article focuses on the picturesqueness of his poetry, the saturation of the poetic world of Renat Kharis with color and light, which make it possible to more accurately and vividly convey the feelings of the poet. Color and light images in the works of Renat Kharis acquire a symbolic sound, and often play the role of Tatar national codes reflect specific native folk light and color traditions and allow you to more vividly convey the feelings of the lyrical character. In the artistic world of Renat Kharis, painting and poetry are closely intertwined, because he is equally professional in both the technique of verse and the brush of fine art. The topic of creativity, the images of artists in the works of Renat Kharis are leitmotifs. The problem of determining the function of light and color images is closely related to the peculiarities of the psychological impact of light and color, as well as to its systematics and symbolism. Color and light images emotionally color Tatar folk holidays, they are used in love lyrics to describe a beloved, in philosophical and patriotic lyrics and poems by Renat Kharis they allow them to more accurately convey the uniqueness of the beauty of the nature of their native land.